Strategy making as iterated processes of resource allocation - Noda, Tomo; Bower, Joseph L. (Strategic Management Journal, 2007)
Capitalizing on the Bower-Burgelman process model of strategy making in a large, complex organization, we investigate the multilevel managerial activities that lead firms facing similar new business opportunities to respond with different strategic commitments. Our field-based data provide evidence on (I) the role of ‘corporate contexts’ that reflects top managers' crude strategic intent in shaping strategic initiatives of business-unit managers; (2) the critical influence of early business development results on increasing or decreasing middle managers' enthusiasm to the new businesses and top managers' confidence in these middle managers in a resource allocation; (3) the escalation or deescalation of a firm's strategic commitment to the new businesses as a consequence of iterations of resource allocation. We conclude that it is useful to conceptualize strategy making in a large, complex firm as an iterated process of resource allocation.